HUBUNGAN KECERDASAN SPIRITUAL TERHADAP AKHLAK MULIA SISWA DI SMP NEGERI 1 CIBUNGBULANG - Amara, Helina; Supriadi, Dedi; Muhlisin, Sofian (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
Spiritual intelligence is a potential that every human being must have. A person is said to have spiritual intelligence if that person is able to place and deal with situations wisely based on the value of faith to obtain happiness both in this world and in the afterlife. Likewise, with noble character, humans can maintain good relations between fellow humans so that humans will live in comfort, affection and hope for the blessing of Allah SWT. If students have good spiritual intelligence then this supports students to have noble character. This research aims to 1) determine the spiritual intelligence of students at SMP Negeri 1 Cibungbulang. 2) knowing the noble character of students at SMP Negeri 1 Cibungbulang. 3) determine the relationship between spiritual intelligence and the noble character of students at SMP Negeri 1 Cibungbulang. The method used in this research is quantitative correlational. This research was carried out at SMP Negeri 1 Cibungbulang from December 2023 to March 2024. The population used was class VIII students, totaling 360 students. The sampling technique used a simple random sample because the research population was more than 100 people, the researchers only took 10% of the total population of 36 students. The results of research using correlation tests using the Pearson correlation formula show that there is a significant relationship between spiritual intelligence and the noble character of students at SMP Negeri 1 Cibungbulang. This test shows that the correlation value for the variables.